2018
DOI: 10.3892/ol.2018.8194
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated overexpression of miR-124 suppresses growth and invasion by targeting JAG1 and EZH2 in gastric cancer

Abstract: Abstract. expression is downregulated and has a tumor suppressor role in various types of cancer. The present study revealed that genes encoding miR-124 were frequently methylated and the expression of miR-124 was downregulated in gastric cancer tissues. Stable expression of miR-124 using a lentiviral vector inhibited gastric cancer cell growth, migration and invasion in vitro. In addition, overexpression of miR-124 suppressed gastric cancer cell xenograft growth in nude mice. The expression of the Notch liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…To enhance our capacity in enhancing miRNA expression, delivery methods including viral vectors have been used. A recent experiment uses lentivirus for delivery of miRNA-124 to down-regulate EZH2 expression and successfully inhibit to gastric cancer progression [ 169 ].…”
Section: Non-coding Rnas and Ezh2 Signalingmentioning
confidence: 99%
“…To enhance our capacity in enhancing miRNA expression, delivery methods including viral vectors have been used. A recent experiment uses lentivirus for delivery of miRNA-124 to down-regulate EZH2 expression and successfully inhibit to gastric cancer progression [ 169 ].…”
Section: Non-coding Rnas and Ezh2 Signalingmentioning
confidence: 99%
“…After transfection, although proliferation curves of all three groups showed an upward trend, cell proliferation rate in miR-124 group was significantly lower than that in NC group and control group, indicating inhibited cell proliferation after miR-124 transfection. Pan et al (20) found that lentiviral vectors that stably express miR124 can inhibit the growth, migration, and invasion of gastric cancer cells. Li et al (21) found that miR-124 can inhibit cell invasion and epithelial mesenchymal transformation by inhibiting Snail2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that miR-124 is also downregulated in gastric cancer cell lines, and the expression of miR-124 has been reported to inhibit growth, decrease colony-forming ability, induce apoptosis, and suppress metastasis and invasion [84][85][86][87][88] (Table 5). In gastric cancer cells, the transfection of miR-124 can reportedly enhance the anticancer effect of 5-fluorouracil [88].…”
Section: Stat3mentioning
confidence: 99%
“…Another frequently reported target gene of miR-124 is the enhancer of zeste homolog 2 (EZH2), which has been found in lung adenocarcinoma [67], hepatocellular carcinoma cancer [87,88], cholangiocarcinoma [107], laryngeal squamous cell carcinoma [114], multiple myeloma [115], and ovarian cancer [23]. EZH2 is reportedly essential for the proliferation of cancer cell lines and for regulating the expression of genes related to EMT [116,117].…”
Section: Target Genes Responsible For the Tumor Suppressor Effect Of Mir-124 Stat3 And Ezh2mentioning
confidence: 99%
See 1 more Smart Citation